Peran Investasi Agrikultur Sebagai Penguat Ketahanan Pangan dari Krisis Iklim - Almughni, Muhammad Afdha Alif; Kusumawardani, Deni; Suyanto, Suyanto (Jurnal Sosial Ekonomi Pertanian, 2024)
The condition of world hunger is very unequal on every continent. The Asian continent is a continent that has a serious famine area after the African continent. This is exacerbated by the food crisis due to the increase in world food prices caused by the COVID-19 pandemic and the conflict between Russia and Ukraine, which is one of the world's suppliers of sunflower, corn, and wheat oil. FAO has mobilized efforts to improve food security and reduce hunger. However, in increasing food production, it also faces the challenge of the climate crisis. In the face of these challenges, FAO has suggested increasing agricultural investment. Therefore, this study aims to determine and analyze the influence of the climate crisis and agricultural investment in Asian countries by using gross domestic product and food inflation as control variables. To investigate the influence of agricultural investment and the climate crisis on food security, the researcher used a quantitative approach with balanced panel data for 42 countries on the Asian continent for the period 2002-2022 using a regression panel. The results showed that the climate crisis with indicators of temperature change and the intensity of extreme events such as drought and flood had a significant negative effect on food security, but changes in rainfall patterns did not affect food security. Other results show that agricultural investment has a significant positive effect on food security.